2017
DOI: 10.1039/c7tc03884d
|View full text |Cite
|
Sign up to set email alerts
|

Cu-Doped nickel oxide prepared using a low-temperature combustion method as a hole-injection layer for high-performance OLEDs

Abstract: Low-temperature combustion methods to deposit s-NiOx and s-Cu-NiOx on ITO glass to fabricate efficient green phosphorescent OLEDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…The process of metal-doping of the electrochromic oxide shows high-performance and reliability has been proposed on tungsten trioxide (WO 3 ) and nickel oxide (NiO) film [11,12]. The chromic mixed metal oxide films often show more natural colors than intrinsic ones in their coloring states.…”
Section: Introductionmentioning
confidence: 99%
“…The process of metal-doping of the electrochromic oxide shows high-performance and reliability has been proposed on tungsten trioxide (WO 3 ) and nickel oxide (NiO) film [11,12]. The chromic mixed metal oxide films often show more natural colors than intrinsic ones in their coloring states.…”
Section: Introductionmentioning
confidence: 99%
“…Ao Liu et al demonstrated the solution combustion synthesis fabrication of optimized 5% Cu doped NiO x films for use in TFT applications, exhibiting excellent electrical performance [49]. Yi-Huan Li et al applied a 300 • C annealing temperature for the solution combustion synthesis of Cu:NiO x , showing that it can be used as an efficient hole injection layer for the fabrication of high performing OLEDs [50]. Thus, solution combustion synthesis metal oxide thin films have emerged as a facile method for the fabrication of functional metal oxide-based charge selective contacts for electronic applications.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the reported results investigate the effect of the thermal annealing temperature (150, 200, and 300 • C) as well as the fuel (acetyl acetonate (Acac)) to oxidizer (Cu and Ni nitrates) ratio (without (w/o), 0.1 and 1.5) in the combustion synthesis process of Cu:NiO x . The study is performed at Cu:NiO x filmswith various final thicknesses (50,200, 300 nm) and for drop-casted bulk Cu:NiO x analogues (with thickness in the range of a few microns). The crystal growth process is studied by performing thermogravimetric analysis (TGA) and the crystallinity of the corresponding Cu:NiO x materials is examined by X-ray diffraction (XRD).…”
Section: Introductionmentioning
confidence: 99%
“…In this report, we propose that the use of suitable Ni-containing solution-processed (SCS) MO interfacial layer between ITO and PEDOT:PSS can be used as a method to improve the properties of the bottom electrode (ITO/MO/PEDOT:PSS). Un-doped spinel nickel cobaltite (NiCo 2 O 4 ) and co-doped with 3% Cu and 2% Li [(Cu-Li):NiCo 2 O 4 ] [ 28 , 29 ] as well as Cu:NiO x and CuO x [ 30 , 31 , 32 ] were used as MOs investigated in the current work. We show that Ni-containing MOs interface modification ITO/MO/PEDOT:PSS improved device performance in normal structure fluorescent super-yellow (SY) OLED devices, in comparison to reference ITO/PEDOT:PSS bottom electrode.…”
Section: Introductionmentioning
confidence: 99%